TESTING OF COMBINED VACCINES AGAINST AUJEZSKY’S DISEASE, PORCINE REPRODUCTIVE AND RESPIRATORY SYNDROME AND PORCINE PARVOVIRUS INFECTION FOR THEIR ANTIGENICITY - Ye. P. Baborenko; Ye. K. Dolganova; K. N. Gruzdev (Ветеринария сегодня)
Tests of inactivated emulsion anti-Aujezsky’s disease, porcine reproductive and respiratory syndrome (PRRS) vaccine based on marker Aujezsky’s disease virus strain, PRRS virus strain and inactivated emulsion anti-Aujezsky’s disease and porcine parvovirus infection vaccine based on marker Aujezsky’s disease virus strain and porcine parvovirus strain developed by the FGBI “ARRIAH” for their antigenicity are described in the paper. It is demonstrated that the said vaccines can be used successfully for PRRS and porcine parvovirus infection and Aujezsky’s disease prevention. They are becoming of special significance when used in programs on Aujeszky’s disease control and eradication. The use of the vaccine based on marker Aujeszky’s disease virus strain allows differentiation between the animals that have antibodies to the marker vaccine strain (in the absence of antibodies to the glycoprotein gE in 100% of cases) from the animals with antibodies to field strains of the Aujeszky’s disease virus in their sera. A comprehensive assessment of the use of associated vaccines developed in the FGBI “ARRIAH” (against Aujeszky’s disease based on the marker strain, reproductive and respiratory syndrome, parvovirus infection), in the framework of anti-epidemic measures on a pig farm of the Russian Federation showed their safety, high antigenicity, immunogenicity.